PENGUKURAN KINERJA MELALUI PENDEKATAN BALANCED SCORECARD PADA PT. PLN (PERSERO) WILAYAH PAPUA CABANG MANOKWARI - Lili Sarce Joi Sapari (Universitas Musamus,Merauke,Papua, 2013)
The purpose of this study are: To determine the performance of PT. PLN (Persero) Branch Papua Manokwari area with balanced scorecard approach. Type of research is descriptive-analytical type. Results showed that 1) Performance of growing and learning with the concept of balanced scorecard has four (4) indicators of employee satisfaction, level of company information, employee turnover and employee productivity levels. From these indicators that need attention by PLN (Persero) Branch Papua Manokwari area for quality improvement is employee satisfaction